دراسة الألفاظ ومعرفة دلالتها على رفع الحديث من عدمه :صحيح البخاري نموذجًا: Study of Terms and Knowing Their Proof on Attributing Hadith or Not: Sahih Al-Bukhari as a Model - Aldabbous, Humood Naef (Online Journal of Research in Islamic Studies, 2022)
The search is a study for terms mentioned in some Hadiths (Prophetic traditions) attributions like the term: “An Alsahabi” :Yobalegh Beh” or “An Alsahabi:Yanmih”, or “An Alsahabi: Rewaya”, and similar terms, and they did not attributed to the Prophet: Mohammad (Peace and blessings of Allah be upon him) and knowing their proof on attributing Hadith or not. I used Sahih Al-Bukhari” as a sample for studying such terms, and my approach in the search based on inductive and analytical approach as I examined Hadith sciences books to investigate sayings of scholars about such terms, as well as examining “Sahih Al-Bukhari”; to see Hadiths in which these terms mentioned, and then I analyzed such combined results and finding out the method of “Sahih Al-Bukhari” in releasing such Hadiths in which attribution such terms mentioned in these Hadiths attribution and knowing if Al-Bukhari narrated these Hadiths with other attributions permitted to attribute Hadith to the Prophet Mohammad (Peace and blessings of Allah be upon him) or not. What make me search in this subject is that in considering such Hadiths that contained these terms in their attribution and did not attributed to the Prophet Mohammad (Peace and blessings of Allah be upon him) we find out that many questions arising to our heads like: are these Hadiths are unreleased or attributed and how can we know that? Is Al-Bukhari, in his Sahih, released some of these Hadiths in which attributions these terms mentioned? And what is the method used by Al-Bukhari in releasing such Hadiths – if any. Such questions made me search in this subject, and to consider scholars opinion in such. The researcher concluded to these terms meant that Hadith is attributed to Prophet Mohammad (Peace and blessings of Allah be upon him) and that all Hadiths mentioned in Sahih Al-Bukhari and in their attributions these terms mentioned and did not attributed to Prophet Mohammad (Peace and blessings of Allah be upon him) that Al-Bukhari mentioned thereof in his Sahih with other attributions having the permission to attribute the Hadith to Prophet Mohammad (Peace and blessings of Allah be upon him).